Effect of Oily waste Water from the Dora Refinery on Some Vegetative Growth Characteristics of Radish (Raphanus sativus L.) - Mohammed, Malak Naeem; Faisal, Maher Zaki (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The study aimed to determine how the oil refinery water affected the growth characteristics of the radish plant. The refinery's water treatment unit's main isolation basins, representing the first factor, pre-treatment water, initiate the cycle, while the final sedimentation basin provides the second factor, post-treatment water. It was used two factors and three replications, with each factor containing seven volumes: 0.00, 0.05, 0.1, 0.15, 0.2, 0.25, and 0.3 Ml/kg. After soil preparation, wastewater was added. It was sowed radish seeds and, after 55 days, doubled the quantity of oil waste water to irrigate the plants. It was harvested the plants during the flowering stage, 129 days after sowing and measured the plant's height, number of leaves, leaf area, total chlorophyll content, root length and diameter, and fresh weight and dry weight. The pre-treatment water had a positive effect on the total chlorophyll content, the length of the roots, and the fresh weight of the root part. These two factors went up by the most, by 12.37%, 26.7%, and 17.05%, respectively. The effect of the pre-treatment water ranged from a decrease to an increase in the average number of leaves, root diameter, fresh weight of the vegetative part, and  dry weight of the vegetative and root parts. While its effect was negative for all volumes in the characteristics of plant height and leaf area, it gave the lowest rate of decrease by 20.2% and 26.63% compared to untreated plants. The post-treatment water had a positive impact on the plant height, number of leaves, total chlorophyll content, and fresh weight of the root part. However, it recorded the highest average increases of 61.26%, 36.12%, 6.71%, and 141.71%. While its effect varied according to the amount of water in terms of leaf area, root length, root diameter, and dry weight of the root part, it gave a negative effect in all treatments in terms of the fresh and dry weight of the vegetative part.